Growth and lactogenic hormones - Matera, Lina; Rapaport, Robert (Neuroimmune biology, 2002)
For more than seventy years evidence has accumulated documenting the existence of a bi-directional communication network between growth hormone and the immune system. In the past twenty years there has been a tremendous proliferation of information detailing the workings of the growth hormone and insulin-like growth factor axis. A multitude of growth factors and binding proteins have been identified. More and more evidence supporting the important role of the growth hormone IGF network in the well functioning of the normal immune system has been documented. Clearly the challenge today is not to prove, but to understand, the neuroimmune regulatory role of GLH in its entire complexity. The ultimate goal of this volume and of all the other volumes of this series is to promote the understanding of the science and to ease human suffering.